(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
Our study investigated the knowledge, attitudes, and perceptions of medical students, residents, and the general public towards medicolegal autopsies in Northern region, India, in the year 2023. Significant disparities were identified in knowledge perspectives, influenced by age. Younger adults, particularly those falling in the age group of 20-29 years showed higher levels of knowledge (35.33%) about autopsies as compared to the older adults falling in the age group of 60 and above showed lower levels of knowledge (100%). Overall, 802 participants (72.6%) had a negative perception in regards to medicolegal autopsy while 302 participants (27.4%)​had a positive perception towards medico legal autopsy. This research study highlights the varying levels of knowledge and perception towards medicolegal autopsies among different age groups, emphasizing the need for targeted educational strategies to bridge the knowledge gaps and calls for collaborative efforts among stakeholders to build public trust, advance forensic medicine practices, and improve public health outcomes.